Prevention of early complications following total hip replacement - Fontalis Andreas (EDP Sciences, 2021)
Total hip arthroplasty (THA) has been quoted as “the operation of the century”, owing to its efficacy and the substantial improvements evidenced with respect to functional patient outcomes and quality of life. However, early postoperative complications are often inevitable, hence it is imperative to take every step to prevent them and minimise morbidity and mortality. This manuscript focuses on the most common early complications following THA, namely venous thromboembolism (VTE), prosthetic joint infection, periprosthetic fracture, instability, and leg length inequality. It aims to outline effective risk stratification strategies and prevention measures that could apply to the wider Orthopaedic community.